Association Between Serum 25-Hydroxy Vitamin D Levels and Blood Pressure Among Adolescents in Two Resource-Limited Settings in Peru - Tomaino, Katherine (Am J Hypertens, 2015)
INTRODUCTION: Serum 25-hydroxyvitamin D (25OHD) deficiency (<50 nmol/l or 20ng/ml) has been associated with increased blood pressure (BP) in observational studies. A paucity of data on this relationship is available in Latin American or child populations. This study investigates the association between 25OHD levels and BP in adolescents at risk for vitamin D deficiency in 2 Peruvian settings. METHODS: In a population-based study of 1,441 Peruvian adolescents aged 13–15 years, 1,074 (75%) provided a serum blood sample for 25OHD analysis and BP measurements. Relationships between 25OHD and BP metrics were assessed using multiple linear regressions, adjusted for anthropometrics and sociodemographic factors. RESULTS: 25OHD deficiency was associated with an elevated diastolic BP (DBP) (1.09mm Hg increase, 95% confidence interval: 0.04 to 2.14; P = 0.04) compared to nondeficient adolescents. Systolic BP (SBP) trended to increase with vitamin D deficiency (1.30mm Hg increase, 95% confidence interval: −0.13 to 2.72; P = 0.08). Mean arterial pressure (MAP) was also greater in adolescents with 25OHD (1.16mm Hg increase, 95% confidence interval: 0.10 to 2.22; P = 0.03). SBP was found to demonstrate a U-shaped relationship with 25OHD, while DBP and MAP demonstrated inverse J-shaped relationships with serum 25OHD status. The association between 25OHD deficiency and BP was not different across study sites (all P ≥ 0.19). DISCUSSION: Adolescents deficient in 25OHD demonstrated increased DBP and MAP and a trend toward increased SBP, when compared to nondeficient subjects. 25OHD deficiency early in life was associated with elevated BP metrics, which may predispose risk of hypertension later in adulthood.